2012
DOI: 10.1164/rccm.201110-1915ci
|View full text |Cite
|
Sign up to set email alerts
|

Anemia in Critical Illness

Abstract: Anemia is common in the intensive care unit, and may be associated with adverse consequences. However, current options for correcting anemia are not without problems and presently lack convincing efficacy for improving survival in critically ill patients. In this article we review normal red blood cell physiology; etiologies of anemia in the intensive care unit; its association with adverse outcomes; and the risks, benefits, and efficacy of various management strategies, including blood transfusion, erythropoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(88 citation statements)
references
References 120 publications
3
85
0
Order By: Relevance
“…Anemia is highly prevalent in critically ill patients but the context in patients with AE remains unclear ( 18 ). A multitude of studies found that up to two-thirds of critically ill patients have a hemoglobin concentration <12 g/dl at ICU admission ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Anemia is highly prevalent in critically ill patients but the context in patients with AE remains unclear ( 18 ). A multitude of studies found that up to two-thirds of critically ill patients have a hemoglobin concentration <12 g/dl at ICU admission ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…This outcome is important because blood transfusion may be associated with worse outcome after oncologic surgery, including long-term survival (35-38). Blood transfusion is not harmless and has been associated with several clinical side effects, including transfusion related acute lung injury and fluid overload (39). In critically ill patients, blood transfusion is associated with poorer outcomes (39).…”
Section: Discussionmentioning
confidence: 99%
“…Blood transfusion is not harmless and has been associated with several clinical side effects, including transfusion related acute lung injury and fluid overload (39). In critically ill patients, blood transfusion is associated with poorer outcomes (39). …”
Section: Discussionmentioning
confidence: 99%
“…Critically ill patients, including those with sepsis, develop anaemia in up to 70% of cases, of which 44-50% will require a blood transfusion [16,17,18]. In septic patients, blood transfusion are required in up to 50% of cases due to a normocytic, normochromic anaemia with low iron, low transferrin but high ferritin, which usually develops through altered iron metabolism and erythropoiesis [17][18][19][20][21][22]. This is due to the inflammatory response stimulated by surgical sepsis and stress leading to elevated inflammatory markers, which inversely correlates with Hb levels [21,23,24].…”
Section: Pathophysiology Of Anaemia In Surgical Stress and Sepsismentioning
confidence: 99%
“…Rogiers et al showed that non-septic critically ill patients had a normal correlation between haematocrit and EPO levels, while septic patients developed more severe anaemia and had lower circulating EPO levels [20]. The inflammatory cytokines IFN-gamma, IL-1 and TNF-alpha have been implicated in the alteration of EPO production [19,25,26]. These inflammatory markers inhibit hypoxiainduced EPO production [25].…”
Section: Altered Erythropoiesismentioning
confidence: 99%